Urinary tract infection in renal transplant recipients - Méndez Chacón, Pedro (2017)
Introduction. Urinary tract infections (UTI) are common among renal transplant recipients (RTR) and their frequency depends on pre- and post-transplant factors. Objectives. To determine the time of appearance of symptomatic UTI among renal transplant recipients, microorganisms causing the infection, and incidence of UTI resistant to antibiotics. Design. Retrospective study. Setting. Renal Transplant Unit, Hospital Edgardo Rebagliati Martins, EsSalud, Lima, Peru. Participants. Patients who have undergone renal transplantation. Interventions. The clinical records of 304 patients subject to kidney transplantation performed between 2002 and 2011 and followed for up to four years were reviewed. There were 215 urine culture-confirmed UTI episodes in 84 transplant recipients. Main outcome measures. Incidence, chronology, microbiological determination/ susceptibility, bacterial resistance, risk factors, diagnostic strategies, presence or absence of bacteremia, and therapeutic management. Results. In 42 of the 84 recipients, the initial episode occurred during the first three months, and 33 (39%) had more than one UTI episode. Bacteria represented the most common etiology (94%), and Escherichia coli was the most prevalent uropathogen, with an extended-spectrum beta-lactamase (ESBL) production rate of 38%, followed by Klebsiella pneumoniae (11%) with an ESBL of 65%. Blood culture was positive in 25 (12%) of the 215 UTI episodes. In 17 recipients (19%), anatomic anomalies of the urinary tract were detected following the transplant. Conclusions. UTI occurred early following kidney transplantation, and Escherichia coli was the most common microorganism found. Antibiotic resistance was present in 79 (37%) of the 215 UTI episodes, representing a continuous challenge in clinical practice.